A fire-resistant cable and its production process

By using modified ceramicized silicone rubber composite belt and crosslinked polyethylene outer sheathing layer in the cable, the problem of insufficient refractory insulation performance of the cable is solved, and the normal operation and fire resistance performance of the cable in the case of fire is achieved.

CN118571576BActive Publication Date: 2025-02-18胜方线缆有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410762355.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-02-18
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The existing cables have insufficient fire resistance and thermal insulation performance, making it difficult to maintain the normal operation of the control system when a fire occurs.

Method used

Use modified ceramicized silicone rubber composite belt as the composite belt layer of the cable. By wrapping the modified ceramicized silicone rubber composite belt in the cable, and extruding and cross-linking polyethylene on the outer layer to form an outer sheath layer to enhance the isolation of the cable. Thermal fire resistance.

Benefits of technology

Improve the thermal insulation and fire resistance of the cable, so that it can maintain normal operation for a period of time when a fire occurs, and avoid heat damage or deformation and breakage of the cable.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of cables, and in particular to a fire-resistant cable and a production process thereof. In the production process of the fire-resistant cable, a composite tape layer is wrapped with a modified ceramic silicone rubber composite tape as a raw material, so that the fire-resistant cable has good heat insulation and fire resistance performance, and the fire-resistant cable has the ability to maintain normal operation when a fire occurs; the modified ceramic silicone rubber composite tape is prepared by pressing a modified rubber mix with a composite glass fiber felt by a cold pressing process and then curing and cross-linking the modified rubber mix by electron beam irradiation; and the modified rubber mix contains platinum particles and a nitrogen-phosphorus-sulfur flame retardant system, so that the ceramicization temperature and carbonization performance of the silicone rubber are effectively improved, so that the silicone rubber has better fire resistance; and the composite glass fiber felt contains alumina aerogel and phase change microcapsules, which have good heat insulation and heat absorption capabilities, can delay the transfer of heat when a fire occurs, and thus the fire-resistant cable has better fire resistance performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of cables, and in particular to a fire-resistant cable and a production process thereof. Background Art

[0002] In order to ensure that the power supply circuits of control, monitoring, guidance and alarm systems can continue to operate normally for a period of time when a fire occurs, the cable needs to have good fire-resistant and heat-insulating properties. Summary of the invention

[0003] The purpose of the present invention is to provide a fire-resistant cable and a production process thereof, which solves the problem that the existing cables have insufficient fire-resistant and heat-insulating properties and also have good flame retardant properties.

[0004] The object of the present invention can be achieved by the following technical scheme: a production process of a fire-resistant cable, comprising the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, twisting, wrapping with mica tape to obtain a wire core, twisting the wire core and wrapping with a modified ceramic silicone rubber composite tape to obtain a composite tape layer to form a cable core, filling the space between the wire core and the modified ceramic silicone rubber composite tape with a glass fiber rope, and then extruding a cross-linked polyethylene outside the composite tape layer by an extruder to form an outer sheath layer, cooling in a water tank, and air-drying in a drying machine to obtain a fire-resistant cable;

[0005] The modified ceramic silicone rubber composite belt is prepared by the following steps:

[0006] Step A1: 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and acetonitrile are mixed, and hexachlorocyclotriphosphazene is added dropwise under the conditions of ultrasonic power of 100 W and temperature of 40°C for reaction for 1-1.5 hours to obtain polymer microspheres;

[0007] The ratio of 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and hexachlorocyclotriphosphazene is 0.01-0.012mol: 0.01-0.012mol: 8-10mL: 0.04-0.045mol;

[0008] During the reaction, under the action of triethylamine, the phenolic hydroxyl groups in 4,4'-dihydroxydiphenyl sulfone and 4,4-sulfonylbis[2-(2-propenyl)]phenol react with the chlorine in hexachlorocyclotriphosphazene to obtain polymer microspheres.

[0009] Step A2: The polymer microspheres, ethylene glycol and deionized water are mixed and ultrasonically dispersed for 20-30 minutes, and under the conditions of a stirring rate of 300-400 rpm and a temperature of 130° C., a chloroplatinic acid aqueous solution is added and reacted for 3-4 hours to obtain loaded microspheres;

[0010] The volume ratio of ethylene glycol to deionized water is 3:2, the mass fraction of chloroplatinic acid aqueous solution is 4%, and the dosage ratio of polymer microspheres to chloroplatinic acid aqueous solution is 1-1.2 g: 8-10 mL;

[0011] During the reaction, since the polymer microspheres contain a large amount of nitrogen, they can provide attachment sites for platinum nanoparticles obtained by reduction, so that the platinum nanoparticles are loaded on the polymer microspheres to obtain loaded microspheres;

[0012] Step A3: adding methyl vinyl silicone rubber, fumed silica, mica powder and hydroxy silicone oil into a mixer, mixing for 8-12 minutes at room temperature, then adding glass powder, magnesium oxide and loaded microspheres, and continuing to mix for 25-30 minutes to obtain a modified rubber mixture, pressing the modified rubber mixture with a composite glass fiber felt through a cold pressing process, and then irradiating the mixture with an electron beam to obtain a modified ceramic silicone rubber composite tape;

[0013] The dosage ratio of methyl vinyl silicone rubber, fumed silica, mica powder, hydroxy silicone oil, glass powder, magnesium oxide and loaded microspheres is 1000-1100g: 130-150g: 300-350g: 20-25g: 170-190g: 95-100g: 10-15g;

[0014] During the reaction, a modified rubber compound containing loaded microspheres is obtained by mixing in a mixer, and then the modified rubber compound is pressed with the composite glass fiber felt by a cold pressing process. Since both the loaded microspheres and the composite glass fiber felt contain unsaturated double bonds, the double bonds in the modified rubber compound are polymerized to form a three-dimensional network structure and solidify by electron beam irradiation. At the same time, the double bonds contained in the modified rubber compound react and cross-link with the double bonds in the composite glass fiber felt to form a covalent bond connection, thereby obtaining a modified ceramic silicone rubber composite tape.

[0015] The composite glass fiber mat is prepared by the following steps:

[0016] Step B1: Graphene oxide, thionyl chloride and N,N-dimethylformamide are mixed and ultrasonically dispersed for 50-60 minutes, and the mixture is reacted for 24 hours at a stirring rate of 600-800 rpm and a temperature of 70° C. to obtain acylated graphene oxide. The acylated graphene oxide and octadecylamine are mixed, and the mixture is reacted for 48 hours at a stirring rate of 300-400 rpm and a temperature of 120° C. to obtain modified graphene oxide;

[0017] The ratio of graphene oxide, thionyl chloride and N,N-dimethylformamide is 2-3 g: 300-400 mL: 5-10 mL, and the ratio of acylated graphene oxide and octadecylamine is 2-3 g: 0.2-0.24 mol;

[0018] During the reaction, the carboxyl groups in the graphene oxide are chlorinated by thionyl chloride to form acyl chloride groups, thereby obtaining acylated graphene oxide. The acyl chloride groups in the acylated graphene oxide then react with the amino groups in octadecylamine to form amides, thereby obtaining modified graphene oxide.

[0019] Step B2: Octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water are mixed, stirred at a stirring rate of 2000 rpm and a temperature of 70°C for 1-1.5 hours, and ammonia water is added to adjust the pH to 8 to obtain an emulsion. Tetraethoxysilane, ethanol and deionized water are mixed, and hydrochloric acid solution is added to adjust the pH to 3. The mixture is stirred at a stirring rate of 300-400 rpm and a temperature of 60°C for 30 minutes to obtain silica sol. The silica sol is slowly dripped into the emulsion, and reacted at a stirring rate of 400-450 rpm and a temperature of 60°C for 24 hours to obtain phase change microcapsules.

[0020] The mass concentration of ammonia water is 25%, the dosage ratio of octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water is 0.02-0.03 mol: 1.2-1.5 g: 0.8-1 g: 0.5-0.8 g: 100-120 mL, the mass fraction of hydrochloric acid solution is 37%, the dosage ratio of tetraethoxysilane, ethanol and deionized water is 10-12 g: 10 g: 20-24 mL, and the dosage ratio of silica sol and emulsion is 60-70 g: 40-45 g;

[0021] During the reaction, an emulsion containing octadecylamine and modified graphene oxide was prepared using emulsifiers dodecylphenol polyoxyethylene ether and hexadecyltrimethylammonium bromide. At the same time, tetraethoxysilane was hydrolyzed under acidic conditions to form silica sol. Then, a phase change microcapsule with silica as the shell material and octadecylamine and modified graphene oxide as the core material was prepared by the sol-gel method.

[0022] Step B3: mixing aluminum nitrate nonahydrate, ethanol and deionized water, stirring at a stirring rate of 300-400 rpm at room temperature for 1.5-2 hours, then adding phase change microcapsules and 3,4-epoxy-1-butene, stirring at a stirring rate of 800-1000 rpm at room temperature for 3-5 minutes to obtain aluminum sol, immersing glass fiber felt in the aluminum sol, aging at room temperature for 24 hours, then adding ethanol solution for aging for 24 hours, and drying to obtain composite glass fiber felt;

[0023] The volume ratio of ethanol to deionized water is 9:1, the volume fraction of the ethanol solution is 20%, and the dosage ratio of aluminum nitrate nonahydrate, phase change microcapsules and 3,4-epoxy-1-butene is 0.1-0.12 mol: 10-12 g: 0.55-0.6 mol;

[0024] During the reaction, aluminum nitrate nonahydrate is hydrolyzed in an ethanol aqueous solution, and then phase change microcapsules and 3,4-epoxy-1-butene are added to obtain aluminum sol. Under acidic conditions, the epoxy group in 3,4-epoxy-1-butene reacts with water to form a hydroxyl group, which participates in and promotes the gelation process of the aluminum sol in the glass fiber mat to form an alumina aerogel wrapped with phase change microcapsules. The gel also contains unsaturated double bonds. After aging, aging and drying, a composite glass fiber mat is obtained.

[0025] Beneficial effects of the invention: The invention relates to the field of cables, and specifically to a fire-resistant cable and a production process thereof. In the preparation process of the fire-resistant cable, a composite tape layer is wrapped with a modified ceramic silicone rubber composite tape as a raw material, so that the fire-resistant cable has good thermal insulation and fire-resistant properties, and the fire-resistant cable has the ability to maintain normal operation for a period of time when a fire occurs; since the modified ceramic silicone rubber composite tape is obtained by pressing the modified rubber compound with the composite glass fiber felt by a cold pressing process and then irradiating it with an electron beam, the modified rubber compound and the composite glass fiber felt are connected by a covalent bond, so that the modified ceramic silicone rubber composite tape has good mechanical properties, and cracks are avoided during the wrapping process, thereby affecting the performance of the fire-resistant cable. In addition, when a fire occurs, a ceramic layer is formed by relying on the glass fiber felt to support the cable, and deformation and fracture of the cable are avoided, thereby affecting its use under fire conditions. Since loaded microspheres are added to the modified rubber compound, the loaded microspheres contain platinum particles and a nitrogen-phosphorus-sulfur flame retardant system, and the presence of the platinum particles makes it possible to effectively Improve the ceramicization temperature of silicone rubber in the modified ceramic silicone rubber composite tape. At the same time, due to the presence of the nitrogen-phosphorus-sulfur flame retardant system, the silicone rubber not only has flame retardant properties, but also the phosphoric acid and sulfuric acid produced by the decomposition of the loaded microspheres promote the degradation of the silicone rubber side chain to produce small molecular substances to form a cross-linked carbon layer, which greatly modifies the carbonization performance of the silicone rubber in the modified ceramic silicone rubber composite tape, promotes the silicone rubber to form a denser fireproof ceramic layer, and makes the fire-resistant cable have better fire resistance. The composite glass fiber felt in the modified ceramic silicone rubber composite tape is a glass fiber felt containing alumina aerogel and wrapped with phase change microcapsules. In the event of a fire, the glass fiber felt containing alumina aerogel can have a good heat insulation effect to avoid damage to the copper conductor of the cable due to heat. At the same time, since the core material in the phase change microcapsule is a mixture of octadecylamine and modified graphene oxide, it has the ability to quickly absorb heat and store a large amount of heat. When a fire occurs, a phase change occurs quickly to absorb heat and reduce heat transfer, so that the fire-resistant cable can maintain a longer service time in a fire. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1 A production process for a fire-resistant cable comprises the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, twisting, wrapping with a commercially available Haoxinyuan 45 mica tape to obtain a wire core, twisting the wire core and wrapping with a modified ceramic silicone rubber composite tape to obtain a composite tape layer to form a cable core, filling the space between the wire core and the modified ceramic silicone rubber composite tape with a commercially available Hengjia glass fiber rope, and then extruding a commercially available Dijie XL140 cross-linked polyethylene outside the composite tape layer through an extruder to form an outer sheath layer, cooling in a water tank, and air-drying in a drying machine to obtain a fire-resistant cable;

[0028] The modified ceramic silicone rubber composite belt is prepared by the following steps:

[0029] Step A1: 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and acetonitrile were mixed, and hexachlorocyclotriphosphazene was added dropwise under the conditions of ultrasonic power of 100 W and temperature of 40°C, and the reaction was carried out for 1 hour to obtain polymer microspheres;

[0030] The ratio of 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and hexachlorocyclotriphosphazene was 0.01 mol: 0.012 mol: 8 mL: 0.04 mol;

[0031] Step A2: polymerized microspheres, ethylene glycol and deionized water were mixed and ultrasonically dispersed for 20 minutes, and then stirred at a stirring rate of 300 rpm and a temperature of 130° C. and an aqueous solution of chloroplatinic acid was added and reacted for 3 hours to obtain loaded microspheres;

[0032] The volume ratio of ethylene glycol to deionized water is 3:2, the mass fraction of chloroplatinic acid aqueous solution is 4%, and the dosage ratio of polymer microspheres to chloroplatinic acid aqueous solution is 1g:8mL;

[0033] Step A3: adding commercially available Xingyan methyl vinyl silicone rubber, commercially available Cabot TS-720 fumed silica, commercially available Lincheng Mineral Mica powder and commercially available Hailan 209 hydroxy silicone oil into a mixer, mixing for 8 minutes at room temperature, then adding commercially available Baiyi glass powder, magnesium oxide and loaded microspheres, and continuing to mix for 25 minutes to obtain a modified rubber mixture, pressing the modified rubber mixture with a composite glass fiber felt through a cold pressing process, and then irradiating it with an electron beam to obtain a modified ceramic silicone rubber composite tape;

[0034] The amount ratio of methyl vinyl silicone rubber, fumed silica, mica powder, hydroxy silicone oil, glass powder, magnesium oxide and loaded microspheres is 1000g: 130g: 300g: 20g: 170g: 95g: 10g;

[0035] The composite glass fiber mat is prepared by the following steps:

[0036] Step B1: commercially available hexachlorobenzene graphite oxide, thionyl chloride and N,N-dimethylformamide were mixed and ultrasonically dispersed for 50 minutes, and reacted for 24 hours at a stirring rate of 600 rpm and a temperature of 70°C to obtain acylated graphene oxide, and acylated graphene oxide was mixed with octadecylamine, and reacted for 48 hours at a stirring rate of 300 rpm and a temperature of 120°C to obtain modified graphene oxide;

[0037] The ratio of graphene oxide, thionyl chloride and N,N-dimethylformamide is 2g:300mL:5mL, and the ratio of acylated graphene oxide and octadecylamine is 2g:0.2mol;

[0038] Step B2: Octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water were mixed, stirred at a stirring rate of 2000 rpm and a temperature of 70°C for 1 hour, and ammonia water was added to adjust the pH to 8 to obtain an emulsion. Tetraethoxysilane, ethanol and deionized water were mixed, and hydrochloric acid solution was added to adjust the pH to 3. The mixture was stirred at a stirring rate of 300 rpm and a temperature of 60°C for 30 minutes to obtain silica sol. The silica sol was slowly dripped into the emulsion, and the mixture was reacted at a stirring rate of 400 rpm and a temperature of 60°C for 24 hours to obtain phase change microcapsules.

[0039] The mass concentration of ammonia water is 25%, the dosage ratio of octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water is 0.02mol:1.2-1.5g:0.8g:0.5g:100mL, the mass fraction of hydrochloric acid solution is 37%, the dosage ratio of tetraethoxysilane, ethanol and deionized water is 10g:10g:20mL, and the dosage ratio of silica sol and emulsion is 60g:40g;

[0040] Step B3: Aluminum nitrate nonahydrate, ethanol and deionized water were mixed, stirred at a stirring rate of 300 rpm at room temperature for 1.5 hours, then phase change microcapsules and 3,4-epoxy-1-butene were added, stirred at a stirring rate of 800 rpm at room temperature for 3 minutes to obtain aluminum sol, commercially available Zhongcai Sanjing glass fiber felt was immersed in the aluminum sol, aged at room temperature for 24 hours, then added with ethanol solution for aging for 24 hours, and dried to obtain a composite glass fiber felt;

[0041] The volume ratio of ethanol to deionized water is 9:1, the volume fraction of the ethanol solution is 20%, and the amount ratio of aluminum nitrate nonahydrate, phase change microcapsules and 3,4-epoxy-1-butene is 0.1 mol:10 g:0.55 mol.

[0042] Example 2 A production process for a fire-resistant cable, comprising the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, twisting, wrapping with a commercially available Haoxinyuan 45 mica tape to obtain a wire core, twisting the wire core and wrapping with a modified ceramic silicone rubber composite tape to obtain a composite tape layer to form a cable core, filling the space between the wire core and the modified ceramic silicone rubber composite tape with a commercially available Hengjia glass fiber rope, and then extruding a commercially available Dijie XL140 cross-linked polyethylene outside the composite tape layer through an extruder to form an outer sheath layer, cooling in a water tank, and air-drying in a drying machine to obtain a fire-resistant cable;

[0043] The modified ceramic silicone rubber composite belt is prepared by the following steps:

[0044] Step A1: 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and acetonitrile were mixed, and hexachlorocyclotriphosphazene was added dropwise under the conditions of ultrasonic power of 100 W and temperature of 40°C, and the reaction was carried out for 1.5 hours to obtain polymer microspheres;

[0045] The ratio of 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and hexachlorocyclotriphosphazene is 0.012mol:0.01mol:10mL:0.04mol;

[0046] Step A2: The polymerized microspheres, ethylene glycol and deionized water were mixed and ultrasonically dispersed for 30 minutes, and then stirred at a stirring rate of 300 rpm and a temperature of 130° C. and an aqueous solution of chloroplatinic acid was added and reacted for 4 hours to obtain loaded microspheres;

[0047] The volume ratio of ethylene glycol to deionized water is 3:2, the mass fraction of chloroplatinic acid aqueous solution is 4%, and the dosage ratio of polymer microspheres to chloroplatinic acid aqueous solution is 1g:8mL;

[0048] Step A3: adding commercially available Xingyan methyl vinyl silicone rubber, commercially available Cabot TS-720 fumed silica, commercially available Lincheng Mineral Mica powder and commercially available Hailan 209 hydroxy silicone oil into a mixer, mixing for 12 minutes at room temperature, then adding commercially available Baiyi glass powder, magnesium oxide and loaded microspheres, and continuing to mix for 30 minutes to obtain a modified rubber mixture, pressing the modified rubber mixture with a composite glass fiber felt through a cold pressing process, and then irradiating it with an electron beam to obtain a modified ceramic silicone rubber composite tape;

[0049] The amount ratio of methyl vinyl silicone rubber, fumed silica, mica powder, hydroxy silicone oil, glass powder, magnesium oxide and loaded microspheres is 1100g: 150g: 300g: 25g: 170g: 100g: 15g;

[0050] The composite glass fiber mat is prepared by the following steps:

[0051] Step B1: commercially available hexachlorobenzene graphite oxide, thionyl chloride and N,N-dimethylformamide were mixed and ultrasonically dispersed for 60 minutes, and reacted for 24 hours at a stirring rate of 800 rpm and a temperature of 70°C to obtain acylated graphene oxide, and acylated graphene oxide was mixed with octadecylamine, and reacted for 48 hours at a stirring rate of 300 rpm and a temperature of 120°C to obtain modified graphene oxide;

[0052] The ratio of graphene oxide, thionyl chloride and N,N-dimethylformamide is 3 g:400 mL:5 mL, and the ratio of acylated graphene oxide and octadecylamine is 2 g:0.24 mol;

[0053] Step B2: Octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water were mixed, stirred at a stirring rate of 2000 rpm and a temperature of 70°C for 1.5 hours, and ammonia water was added to adjust the pH to 8 to obtain an emulsion. Tetraethoxysilane, ethanol and deionized water were mixed, and hydrochloric acid solution was added to adjust the pH to 3. The mixture was stirred at a stirring rate of 400 rpm and a temperature of 60°C for 30 minutes to obtain silica sol. The silica sol was slowly dripped into the emulsion, and reacted at a stirring rate of 450 rpm and a temperature of 60°C for 24 hours to obtain phase change microcapsules.

[0054] The mass concentration of ammonia water is 25%, the dosage ratio of octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water is 0.03 mol: 1.2-1.5 g: 0.8 g: 0.8 g: 120 mL, the mass fraction of hydrochloric acid solution is 37%, the dosage ratio of tetraethoxysilane, ethanol and deionized water is 12 g: 10 g: 20 mL, and the dosage ratio of silica sol and emulsion is 70 g: 40 g;

[0055] Step B3: Aluminum nitrate nonahydrate, ethanol and deionized water are mixed, stirred at a stirring rate of 400 rpm and room temperature for 1.5-2 hours, then phase change microcapsules and 3,4-epoxy-1-butene are added, stirred at a stirring rate of 800 rpm and room temperature for 5 minutes to obtain aluminum sol, commercially available Zhongcai Sanjing glass fiber felt is immersed in the aluminum sol, aged at room temperature for 24 hours, then added with ethanol solution for aging for 24 hours, and dried to obtain a composite glass fiber felt;

[0056] The volume ratio of ethanol to deionized water is 9:1, the volume fraction of the ethanol solution is 20%, and the amount ratio of aluminum nitrate nonahydrate, phase change microcapsules and 3,4-epoxy-1-butene is 0.12 mol:12 g:0.55 mol.

[0057] Example 3 A production process for a fire-resistant cable, comprising the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, twisting, wrapping with a commercially available Haoxinyuan 45 mica tape to obtain a wire core, twisting the wire core and wrapping with a modified ceramic silicone rubber composite tape to obtain a composite tape layer to form a cable core, filling the space between the wire core and the modified ceramic silicone rubber composite tape with a commercially available Hengjia glass fiber rope, and then extruding a commercially available Dijie XL140 cross-linked polyethylene outside the composite tape layer through an extruder to form an outer sheath layer, cooling in a water tank, and air-drying in a drying machine to obtain a fire-resistant cable;

[0058] The modified ceramic silicone rubber composite belt is prepared by the following steps:

[0059] Step A1: 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and acetonitrile were mixed, and hexachlorocyclotriphosphazene was added dropwise under the conditions of ultrasonic power of 100 W and temperature of 40°C, and the reaction was carried out for 1.5 hours to obtain polymer microspheres;

[0060] The ratio of 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and hexachlorocyclotriphosphazene is 0.012mol:0.012mol:10mL:0.045mol;

[0061] Step A2: polymerized microspheres, ethylene glycol and deionized water were mixed and ultrasonically dispersed for 30 minutes, stirred at a stirring rate of 400 rpm and a temperature of 130° C., and chloroplatinic acid aqueous solution was added and reacted for 4 hours to obtain loaded microspheres;

[0062] The volume ratio of ethylene glycol to deionized water is 3:2, the mass fraction of chloroplatinic acid aqueous solution is 4%, and the dosage ratio of polymer microspheres to chloroplatinic acid aqueous solution is 1.2 g:10 mL;

[0063] Step A3: adding commercially available Xingyan methyl vinyl silicone rubber, commercially available Cabot TS-720 fumed silica, commercially available Lincheng Mineral Mica powder and commercially available Hailan 209 hydroxy silicone oil into a mixer, mixing for 12 minutes at room temperature, then adding commercially available Baiyi glass powder, magnesium oxide and loaded microspheres, and continuing to mix for 30 minutes to obtain a modified rubber mixture, pressing the modified rubber mixture with a composite glass fiber felt through a cold pressing process, and then irradiating it with an electron beam to obtain a modified ceramic silicone rubber composite tape;

[0064] The amount ratio of methyl vinyl silicone rubber, fumed silica, mica powder, hydroxy silicone oil, glass powder, magnesium oxide and loaded microspheres is 1100g: 150g: 350g: 25g: 190g: 100g: 15g;

[0065] The composite glass fiber mat is prepared by the following steps:

[0066] Step B1: commercially available hexachlorobenzene graphite oxide, thionyl chloride and N,N-dimethylformamide were mixed and ultrasonically dispersed for 60 minutes, and reacted for 24 hours at a stirring rate of 800 rpm and a temperature of 70°C to obtain acylated graphene oxide, and acylated graphene oxide was mixed with octadecylamine, and reacted for 48 hours at a stirring rate of 400 rpm and a temperature of 120°C to obtain modified graphene oxide;

[0067] The ratio of graphene oxide, thionyl chloride and N,N-dimethylformamide is 3 g:400 mL:10 mL, and the ratio of acylated graphene oxide and octadecylamine is 3 g:0.24 mol;

[0068] Step B2: Octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water were mixed, stirred at a stirring rate of 2000 rpm and a temperature of 70°C for 1.5 hours, and ammonia water was added to adjust the pH to 8 to obtain an emulsion. Tetraethoxysilane, ethanol and deionized water were mixed, and hydrochloric acid solution was added to adjust the pH to 3. The mixture was stirred at a stirring rate of 400 rpm and a temperature of 60°C for 30 minutes to obtain silica sol. The silica sol was slowly dripped into the emulsion, and reacted at a stirring rate of 450 rpm and a temperature of 60°C for 24 hours to obtain phase change microcapsules.

[0069] The mass concentration of ammonia water is 25%, the amount ratio of octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water is 0.03mol:1.5g:1g:0.8g:120mL, the mass fraction of hydrochloric acid solution is 37%, the amount ratio of tetraethoxysilane, ethanol and deionized water is 12g:10g:24mL, and the amount ratio of silica sol and emulsion is 70g:45g;

[0070] Step B3: Aluminum nitrate nonahydrate, ethanol and deionized water were mixed, stirred at a stirring rate of 400 rpm and room temperature for 2 hours, then phase change microcapsules and 3,4-epoxy-1-butene were added, stirred at a stirring rate of 1000 rpm and room temperature for 5 minutes to obtain aluminum sol, commercially available Zhongcai Sanjing glass fiber felt was immersed in the aluminum sol, aged at room temperature for 24 hours, then added with ethanol solution for aging for 24 hours, and dried to obtain a composite glass fiber felt;

[0071] The volume ratio of ethanol to deionized water is 9:1, the volume fraction of the ethanol solution is 20%, and the amount ratio of aluminum nitrate nonahydrate, phase change microcapsules and 3,4-epoxy-1-butene is 0.12 mol:12 g:0.6 mol.

[0072] Comparative Example 1 Compared with Example 3, this comparative example is different in that 4,4-sulfonylbis[2-(2-propenyl)]phenol is replaced by 4,4'-dihydroxydiphenyl sulfone in the preparation process of the modified ceramic silicone rubber composite tape in Example 3, and the other steps are the same.

[0073] Comparative Example 2 Compared with Example 3, this comparative example is different in that the loaded microspheres in the preparation process of the modified ceramic silicone rubber composite tape in Example 3 are replaced with the polymerized microspheres in Example 3, and the other steps are the same.

[0074] Comparative Example 3 Compared with Example 3, this comparative example is different in that the modified graphene oxide in the preparation process of the composite glass fiber mat in Example 3 is replaced by octadecylamine, and the other steps are the same.

[0075] Comparative Example 4 Compared with Example 3, this comparative example replaces the composite glass fiber felt in the preparation process of the modified ceramic silicone rubber composite tape in Example 3 with the commercially available Zhongcai Sanjing glass fiber felt, and the other steps are the same.

[0076] Take the modified ceramic silicone rubber composite tape and the fire-resistant cable prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, refer to GB / T 2406.2-2009, make the modified ceramic silicone rubber composite tape into a 80 mm × 10 mm sample, use a limiting oxygen index instrument to test the sample, test its limiting oxygen index, refer to GB / T 2408-2021, make it into a 125 mm × 13 mm sample, use a horizontal vertical combustion tester to perform a vertical combustion test on it, evaluate its combustion grade, refer to GB / T 19216.21-2003, the fire-resistant cable is made into 1200mm samples, and its qualification is judged by observing whether the bulb goes out after the fire supply and cooling. The initial fire supply time is 90min, and the cooling time is 15min. If the test is qualified, that is, the bulb is not extinguished, then the fire supply time is increased by 10min, and the cooling time remains unchanged until the test fails, that is, the bulb goes out. The fire supply time when the bulb goes out is used as the judgment of its fire resistance performance. The test results are shown in Table 1 Performance test results table:

[0077] Table 1 Performance test results

[0078] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Limiting oxygen index (%) 34.1 34.5 34.7 34.6 32.3 34.4 29.7 Combustion level V-0 V-0 V-0 V-2 V-1 V-0 V-2 Light supply time when the lamp is off (min) 160 160 160 150 110 130 90

[0079] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 replaces 4,4-sulfonylbis[2-(2-propylene)]phenol with 4,4'-dihydroxydiphenyl sulfone in the preparation process of the modified ceramic silicone rubber composite tape in Example 3. Due to the lack of double bonds, there is no covalent bond between the modified rubber compound and the composite glass fiber mat, which leads to a decrease in its combustion grade. Comparative Example 2 replaces the loaded microspheres in the preparation process of the modified ceramic silicone rubber composite tape in Example 3 with the polymerized microspheres in Example 3. Due to the lack of platinum The presence of the element leads to a decrease in the ceramicization temperature and post-ceramic performance of the ceramicized silicone rubber, which in turn affects its fire resistance. In Comparative Example 3, the modified graphene oxide in the preparation process of the composite glass fiber felt in Example 3 is replaced by octadecylamine. Due to the lack of doping with modified graphene oxide, the phase change performance of its phase change microcapsules is reduced, which in turn affects its fire resistance. In Comparative Example 4, the composite glass fiber felt in the preparation process of the modified ceramic silicone rubber composite belt in Example 3 is replaced by the commercially available Zhongcai Sanjing glass fiber felt. Due to the lack of alumina gel and composite microcapsules on the glass fiber felt, its various performances are significantly reduced.

[0080] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0081] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A production process for a fire-resistant cable, characterized in that: The method comprises the following steps: adding round copper wire to a wire drawing machine, drawing, annealing, twisting, wrapping with mica tape to obtain a wire core, twisting the wire core and wrapping with a modified ceramic silicone rubber composite tape to obtain a composite tape layer to form a cable core, filling the space between the wire core and the modified ceramic silicone rubber composite tape with a glass fiber rope, and then extruding a cross-linked polyethylene outside the composite tape layer through an extruder to form an outer sheath layer, cooling in a water tank, and air-drying in a drying machine to obtain a fire-resistant cable; The modified ceramic silicone rubber composite belt is prepared by the following steps: Step A1: 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and acetonitrile are mixed, and hexachlorocyclotriphosphazene is added dropwise under the conditions of ultrasonic power of 100 W and temperature of 40°C for reaction for 1-1.5 hours to obtain polymer microspheres; Step A2: The polymer microspheres, ethylene glycol and deionized water are mixed and ultrasonically dispersed for 20-30 minutes, and under the conditions of a stirring rate of 300-400 rpm and a temperature of 130° C., a chloroplatinic acid aqueous solution is added and reacted for 3-4 hours to obtain loaded microspheres; Step A3: adding methyl vinyl silicone rubber, fumed silica, mica powder and hydroxy silicone oil into a mixer, mixing for 8-12 minutes at room temperature, then adding glass powder, magnesium oxide and loaded microspheres, and continuing to mix for 25-30 minutes to obtain a modified rubber mixture, pressing the modified rubber mixture with a composite glass fiber felt through a cold pressing process, and then irradiating the mixture with an electron beam to obtain a modified ceramic silicone rubber composite tape; The composite glass fiber mat is prepared by the following steps: Step B1: Graphene oxide, thionyl chloride and N,N-dimethylformamide are mixed and ultrasonically dispersed for 50-60 minutes, and the mixture is reacted for 24 hours at a stirring rate of 600-800 rpm and a temperature of 70° C. to obtain acylated graphene oxide. The acylated graphene oxide and octadecylamine are mixed, and the mixture is reacted for 48 hours at a stirring rate of 300-400 rpm and a temperature of 120° C. to obtain modified graphene oxide; Step B2: Octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water are mixed, stirred at a stirring rate of 2000 rpm and a temperature of 70°C for 1-1.5 hours, and ammonia water is added to adjust the pH to 8 to obtain an emulsion. Tetraethoxysilane, ethanol and deionized water are mixed, and hydrochloric acid solution is added to adjust the pH to 3. The mixture is stirred at a stirring rate of 300-400 rpm and a temperature of 60°C for 30 minutes to obtain silica sol. The silica sol is slowly dripped into the emulsion, and reacted at a stirring rate of 400-450 rpm and a temperature of 60°C for 24 hours to obtain phase change microcapsules. Step B3: Mix aluminum nitrate nonahydrate, ethanol and deionized water, stir for 1.5-2 hours at a stirring rate of 300-400 rpm at room temperature, then add phase change microcapsules and 3,4-epoxy-1-butene, stir for 3-5 minutes at a stirring rate of 800-1000 rpm at room temperature to obtain aluminum sol, immerse glass fiber felt in the aluminum sol, age at room temperature for 24 hours, then add ethanol solution for aging for 24 hours, and dry to obtain composite glass fiber felt.

2. The production process of a fire-resistant cable according to claim 1, characterized in that: In step A1, the ratio of 4,4'-dihydroxydiphenyl sulfone, 4,4-sulfonylbis[2-(2-propenyl)]phenol, triethylamine and hexachlorocyclotriphosphazene is 0.01-0.012 mol: 0.01-0.012 mol: 8-10 mL: 0.04-0.045 mol.

3. The production process of a fire-resistant cable according to claim 1, characterized in that: In step A2, the volume ratio of ethylene glycol to deionized water is 3:2, the mass fraction of the chloroplatinic acid aqueous solution is 4%, and the amount ratio of the polymer microspheres to the chloroplatinic acid aqueous solution is 1-1.2 g: 8-10 mL.

4. The production process of a fire-resistant cable according to claim 1, characterized in that: In step A3: the usage ratio of methyl vinyl silicone rubber, fumed silica, mica powder, hydroxy silicone oil, glass powder, magnesium oxide and loaded microspheres is 1000-1100 g: 130-150 g: 300-350 g: 20-25 g: 170-190 g: 95-100 g: 10-15 g.

5. The production process of a fire-resistant cable according to claim 1, characterized in that: In step B1: the ratio of graphene oxide, thionyl chloride and N,N-dimethylformamide is 2-3 g: 300-400 mL: 5-10 mL, and the ratio of acylated graphene oxide and octadecylamine is 2-3 g: 0.2-0.24 mol.

6. The production process of a fire-resistant cable according to claim 1, characterized in that: In step B2, the mass concentration of ammonia water is 25%, the amount ratio of octadecylamine, modified graphene oxide, dodecylphenol polyoxyethylene ether, hexadecyltrimethylammonium bromide and deionized water is 0.02-0.03 mol: 1.2-1.5 g: 0.8-1 g: 0.5-0.8 g: 100-120 mL, the mass fraction of hydrochloric acid solution is 37%, the amount ratio of tetraethoxysilane, ethanol and deionized water is 10-12 g: 10 g: 20-24 mL, and the amount ratio of silica sol and emulsion is 60-70 g: 40-45 g.

7. The production process of a fire-resistant cable according to claim 1, characterized in that: In step B3: the volume ratio of ethanol to deionized water is 9:1, the volume fraction of the ethanol solution is 20%, and the amount ratio of aluminum nitrate nonahydrate, phase change microcapsules and 3,4-epoxy-1-butene is 0.1-0.12 mol: 10-12 g: 0.55-0.6 mol.

8. A fire-resistant cable, characterized in that: Prepared according to any one of the production processes described in claims 1-7.

Citation Information

Patent Citations

  • Preparation method and application of modified graphene oxide

    CN106117065A

  • Preparation method and application of high-temperature-resistant aerogel composite material

    CN116606120A